The relationship of parenting patterns to the growth and development of children aged 2-4 years - Yesi Safitri; Nidatul Khofiyah (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Early childhood growth and development constitute a crucial period that determines the quality of human resources in the future. However, problems related to growth and development are still frequently found among children under five years of age. Based on data from the Yogyakarta Health Office in 2023, derived from 2022 records, the coverage of growth and development monitoring among children under five reached 53.3%. This percentage indicates that the coverage has not yet met the 2023 strategic plan target of 85%. One environmental factor that influences children’s growth and development is parenting style. In this context, inappropriate parenting practices can lead to suboptimal physical growth and developmental outcomes in children. Purpose: to analyze the relationship between parenting style and the growth and development of children aged 2-4 years. Method: This study employed a quantitative approach using a descriptive correlational design with a cross-sectional method. The research population consisted of all children aged 2-4 years in the working area of Puskesmas (Community Health Center) Kasihan II, totaling 938 children. A sample of 100 respondents was selected using proportional stratified sampling and cluster random sampling techniques. Data were collected using standardized instruments. Parenting style was measured using the PSDQ questionnaire, child growth was assessed using the weight-for-age (WFA) indicator, and child development was evaluated using the KPSP instrument. Data analysis was conducted using the Spearman rank test at a significance level of <0.05. Results: The results showed a significant relationship between parenting style and child growth (p = 0.000; r= 0.376) as well as child development (p= 0.000; r = 0.646). Conclusion: Democratic parenting is most effective in supporting the growth and development of children aged 2-4 years. Most children experience normal growth and development. There is a significant relationship between parenting and growth. Suggestion: Parents are expected to adopt a democratic parenting style to support optimal child growth and development.